Ilmu jiwa agama - Zakiah Darajat (Bulan Bintang, 1970)
sgh c1/oen, c.2; nr c.3-4,budi, c.5/oen, c.6,ws.7-11/oen, c.12/sgh c13/ir,c.14/oen, c.15/ir,c.16/ast c.17/tr, c.18-28/stoc6, c.1/stoc3=c.2-26/stoc6=c.27